VULCÂNICAS POTÁSSICAS INTEMPERIZADAS COMO PROTÓLITOS DOS FILITOS HEMATÍTICOS DA SERRA DO ESPINHAÇO MERIDIONAL (MINAS GERAIS) - Chaves, Alexandre de Oliveira; Knauer, Luiz Guilherme (Geochimica Brasiliensis, 2020)
The hematitic phyllite is a rock that occurs in the São João da Chapada and Sopa-Brumadinho formations of the southern Espinhaço range. Its origin is widely discussed in papers on Espinhaço, but there is no consensus on its protolith due to certain characteristics of the lithotype, such as its chemical composition and textural features. The pattern of rare earth elements strongly enriched [(La/Yb)N 6.80-17.68], with light rare earth elements [(La/Sm)N 2.54-4.83] richer than heavy ones [(Gd/Yb)N 1.28-3,32], suggests that the protolith was an alkaline volcanic rock formed during the rift that generated the Espinhaço basin. The major elements indicate that the alkaline rock met weathering processes, becoming a regolith. During the Brasiliano metamorphism, it finally became hematitic phyllite. Other characteristics of the lithotype, such as the presence of sericite-bearing rounded parts (possibly formed by alteration and deformation of leucite crystals) and the preservation of igneous layering, suggest a potassic volcanic origin for hematitic phyllite. In diagram that allows identifying altered and metamorphic volcanic rocks, the investigated samples have composition similar to a feldspathoid-rich alkali-basalt, probably a leucite tephrite, or even a leucitite, rocks from mantle source.